Response of Eichhornia crassipes weeds to various doses of florpyrauxifen-benzyl herbicide application in cirata reservoir, Cianjur regency: English - Nita Nur Rezkia; Denny Kurniadie; Umar Dani (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2025)
The water hyacinth (E.crassipes) invasion has created a concerning ecological crisis in Cirata Reservoir, which is home to Southeast Asia's largest hydroelectric power plant and threatening the balance of freshwater ecosystems. Florpyrauxifen-benzyl herbicide emerges as a potential solution due to its high effectiveness and biodegradable nature. This study looked for to evaluate the efficacy of the herbicide containing Florpyrauxifen-benzyl in mitigating the presence of water hyacinth weeds at Cirata Reservoir, Cianjur Regency. This study utilized a Randomized Block Design containing four replications and seven treatments, including herbicide doses of 500, 750, 1000, 1250, and 1500 ml/ha, compared with hand weeding and control (without herbicide). Results showed that Florpyrauxifen-benzyl herbicide effectively suppressed water hyacinth growth up to 12 weeks after application (WAA). All tested herbicide doses resulted in lower weed biomass and weed damage percentage reaching 100% compared to control and hand weeding treatments. This study concludes that Florpyrauxifen-benzyl herbicide at doses of 500-1500 ml/ha effectively controls water hyacinth weeds in freshwater ecosystems, also providing a potential solution to the invasive aquatic weed problem at Cirata Reservoir.